Analysis of Oral Chronic Kidney Disease with Hemodialysis Therapy in South Kalimantan - Indonesia - Isnur Hatta; Khairunnisa Amalia Pratami; Maharani Laillyza Apriasari (Berkala Kedokteran, 2019)
Abstract: Chronic kidney disease (CKD) is a world health problem where the incidence continues to increase, has a poor prognosis and high-level financing. Clinical manifestations of the oral cavity can occur in CKD patients with hemodialysis therapy due to a decrease in the immune system. To analyze the descriptively the clinical manifestations of oral cavity in CKD patients with hemodialysis therapy at RSUD Ulin Banjarmasin South Kalimantan, period January-March 2019. This is a descriptive analysis with a cross sectional study design, based on history and clinical examination of the oral cavity. Data was entered and analyzed using chi square test. Sampling by purposive sampling. there is a relationship between uremic odor and duration of hemodialysis (p = 0.017). There was a relationship between xerostomia and gender (p = 0.035) and there was a relationship between xerostomia and the duration of hemodialysis (p = 0.007). There is a relationship between gingival swelling and age (p = 0.010) and there is a relationship between gingival swelling and diabetes mellitus (p = 0,000). Manifestations found in the oral cavity of CKD patients with hemodialysis therapy are uremic odor, mouthache, xerostomia, mucosal lesions, candidiasis, and gingival swelling. There is a relationship between sex with xerostomia, the relationship between age with gingival swelling, the relationship between the duration of hemodialysis with uremic odor and xerostomia, the association between DM with gingival swelling. Keywords: Chronic Kidney Disease, Clinical Manifestations, Hemodialysis, Oral Cavity